Vaccinations against smallpox and tuberculosis are associated with better long-term survival: a Danish case-cohort study 1971–2010. (5th July 2016) - Rieckmann, Andreas; Villumsen, Marie; Sørup, Signe; Haugaard, Line Klingen; Ravn, Henrik; Roth, Adam; Baker, Jennifer Lyn; Benn, Christine Stabell; Aaby, Peter
Abstract: Background: When vaccinations with vaccinia against smallpox and Bacillus Calmette-Guérin (BCG) against tuberculosis were phased out in some high-income countries around 1980, the impact on overall mortality was not examined. Recent studies from low-income countries have suggested that these vaccines are associated with mortality reductions, not explained by specific disease protection. We examined whether vaccinia and BCG administered in childhood were associated with long-term mortality reductions in a high-income population. Methods: In this case-cohort study, we followed 47 622 schoolchildren from Copenhagen, Denmark, born 1965 to 1976, from their first health examination to 2010. This cohort experienced the phase-out of vaccinia and BCG vaccination programmes. Results: A sub-cohort of 5 316 individuals (699 excluded) was followed for 164 450 person-years (0.2% were lost to follow-up), and 401 deaths due to natural causes (841 deaths in total) occurred in the full cohort. Compared with individuals who had not received vaccinia or BCG, those who had received both vaccinia and BCG had an adjusted hazard ratio (aHR) of 0.54 [95% confidence interval (CI): 0.36–0.81] for mortality due to natural causes of death; those who only received BCG had an aHR of 0.58 (95% CI: 0.39–0.85). Vaccinia and BCG were not associated with any protection against deaths by accidents, suicide or murder, the combined aHR being 0.94 (95% CI: 0.62–1.42). Conclusions: Vaccinia and BCG vaccinations were associated with better long-term survival, which was not explained by specific protection. Vaccines with beneficial non-specific effects may reduce overall mortality even after the target diseases are eradicated.